2022
DOI: 10.1021/acs.biochem.2c00091
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of the Flexible Cardiac Troponin T Linker Domain in a Fully Reconstituted Thin Filament

Abstract: The structural analysis of large protein complexes has been greatly enhanced through the application of electron microscopy techniques. One such multiprotein complex, the cardiac thin filament (cTF), has cyclic interactions with thick filament proteins to drive contraction of the heart that has recently been the subject of such studies. As important as these studies are, they provide limited or no information on highly flexible regions that in isolation would be characterized as inherently disordered. One such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…5B to D, red and blue atoms, respectively) that link it to both C-terminal and N-terminal parts of Tm that form the overlap region. TnT1 also plays a role in the cooperativity between the two strands of Tm ( 6 , 46 ), since its interaction with the junction region on the opposite strand of the TF provides a physical link between the two TF stands via TnT1 linker region ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…5B to D, red and blue atoms, respectively) that link it to both C-terminal and N-terminal parts of Tm that form the overlap region. TnT1 also plays a role in the cooperativity between the two strands of Tm ( 6 , 46 ), since its interaction with the junction region on the opposite strand of the TF provides a physical link between the two TF stands via TnT1 linker region ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…TnT has two IDR regions. The first is a ∼50 residue linker (approximately residues R158–Q203) between two structured motifs ( Deranek et al, 2022 ). Cross-linking mass spectroscopy (MS) shows that the binding of TnT’s intrinsically disordered C-terminus to TnC contributes to force generation in the myofilament ( Johnston et al, 2019 ).…”
Section: Myofilament-associated Protein With Intrinsic Disorder (Mapid)smentioning
confidence: 99%
“…Cross-linking mass spectroscopy (MS) shows that the binding of TnT’s intrinsically disordered C-terminus to TnC contributes to force generation in the myofilament ( Johnston et al, 2019 ). Using Foerster resonance energy transfer (FRET) and molecular dynamics (MD) simulations, the linker’s conformational ensembles on the full cardiac thin filament have been elucidated ( Deranek et al, 2022 ). The second region is the C-terminus of TnT, which has been predicted to be an IDR ( Na et al, 2016 ), and confirmed by our PONDR results in Fig.…”
Section: Myofilament-associated Protein With Intrinsic Disorder (Mapid)smentioning
confidence: 99%
See 2 more Smart Citations